PROSPECTS FOR PROCESSING OF THE KRESTOVOZDVIZHENSKAYA PLACER DUMPS - Goldyrev, V. V.; Ilaltdinov, I. Ya; Osovetskiy, B. M.; Plyusnina, K. I. (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2022)
The main features of the structure and gold content of the dumps of the Krestovozdvizhenskaya placer in the Middle Urals are considered. Infofrmation on drilling operations performed, gold concentration, morphological features, granulometric, and chemical composition of metal particles are presented. The studies revealed the presence of the dumps body areas with gold content identical to conditions for modern placers. The dimension of the most gold particles makes it possible to apply the hydraulic method for their industrial extraction. Characteristic evidence of a gold long stay in dumps (the formation of a high-grade coat, deposits and films on the surface, intergrowths and "gold" conglomerates, gold intermetallic compounds) are noted. Possible ways of organizing the processing of dumps are proposed.